2020
DOI: 10.3390/plants9070845
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Lipid Alterations in Response to Heat Stress of Arabidopsis thaliana

Abstract: In response to elevated temperatures, plants alter the activities of enzymes that affect lipid composition. While it has long been known that plant leaf membrane lipids become less unsaturated in response to heat, other changes, including polygalactosylation of galactolipids, head group acylation of galactolipids, increases in phosphatidic acid and triacylglycerols, and formation of sterol glucosides and acyl sterol glucosides, have been observed more recently. In this work, by measuring lipid levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 62 publications
3
51
3
Order By: Relevance
“…Muller et al 21,22 reported that the accumulation of TAG species, particularly those with polyunsaturated acyl chains, is a heat-response mechanism. The TAG formed in peanut anthers under HT contained all the major fatty acids but was less enriched in 18:3 than in the other major fatty acids, in contrast to the results in Arabidopsis [21][22][23][24] . Essentially no TAG(18:3/18:3/18:3) was accumulated under HT in peanut anthers (Fig.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Muller et al 21,22 reported that the accumulation of TAG species, particularly those with polyunsaturated acyl chains, is a heat-response mechanism. The TAG formed in peanut anthers under HT contained all the major fatty acids but was less enriched in 18:3 than in the other major fatty acids, in contrast to the results in Arabidopsis [21][22][23][24] . Essentially no TAG(18:3/18:3/18:3) was accumulated under HT in peanut anthers (Fig.…”
Section: Discussioncontrasting
confidence: 90%
“…5 and Supplementary Table S3). This is in contrast to data from Arabidopsis leaves and seedlings, where 18:3/18:3/18:3 levels are highly increased in leaves under short-term heat stress [21][22][23][24] . SPT 06-07 had a larger percent increase under HT than Bailey for most TAG species (Fig.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Biotic and abiotic stresses result in dramatic fluctuations in chloroplast lipid levels, with head-group acylation being strongly enhanced by stress ( Figure 3 ). Whereas wounding and freeze-thaw treatments have been shown to increase the level of acylated lipids in a number of plant species, most studies of stress effects on chloroplast lipid acylation have been done in Arabidopsis thaliana [ 7 , 8 , 10 , 16 , 20 , 22 , 23 , 28 , 33 ]. The pattern of acylated chloroplast lipid accumulation varies as a function of the particular stress applied to Arabidopsis plants.…”
Section: Varied Patterns Of Acylated Chloroplast Lipids Are Inducementioning
confidence: 99%